PREVALENCE AND FACTORS ASSOCIATED WITH SHEESHA SMOKING IN A SAMPLE OF MEDICAL STUDENTS - Babar, Nabeela Fazal; Riaz, Saadia (Journal of Postgraduate Medical Institute, 2015)
Objective: To determine the prevalence of sheesha smokers among medical students and to examine the factors associated with sheesha smoking. Methodology: A total of 578 medical students from both public & private sector in Rawalpindi were selected by consecutive sampling technique. Pre -formed & pretested questionnaire was administered to them after assuring of confidentiality & taking their informed verbal consent. Results: Five seventy eight medical students were administered question -naire, 207 (36%) of them confessed that they smoke sheesha, 82(39.42%) out of them were regular sheesha smokers while 125(60.09%) said they smoke sheesha occasionally. Out of 207sheesha smokers 84(40.5%) started for fun sake, 39(19.5%) out of curiosity, 56 (27%) for style 28 (13.5%) started smoking sheesha because of peer pressure. Of smokers 123(59%) believed that shee -sha smoking was less harmful than cigarette. 69 (33%) of sheesha smokers had no plans to quit sheesha smoking. Conclusion: Lack of correct information & mistaken believe that sheesha smoking is less harmful than other methods of tobacco smoking is reason for its high use among youth. Moreover its easy availability at restaurants and cafés has made it a social activity that promises both pleasure & entertain-ment.